AN ASSESSMENT ON READABILITY OF READING TEXT IN ENGLISH SUMMATIVE TEST FOR FIFTH GRADE SMP NEGERI TOMPASO - Risky Langi; Nihta V. F Liando; Sanerita Tresnawati Olii (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The present study dealt with the research problem: Are reading texts in 2020 summative assessment for fifth semester students at SMP Negeri Tompaso readable assessed using Flesch reading ease formula? The study is a quantitative content analysis with fifth semester summative test as the source of data. The data were reading texts with more than 100 words in length. The data were analyzed quantitatively using automatic online readability checker. Result of the data analysis indicates that of 6 reading texts that are analyzed, four (text 1, 2, 5 and 6) ranged from 79.4 (fairly easy to read) to 90.4 (very easy to read), one (66. I) is moderate or average, and still one (39.6) (3) is difficult to read. It can be concluded that only one of the analyzed texts is appropriate for the target students or test-takers. Consequently, test items assessing reading comprehension ability do not yield students reading ability properly.